Canned corned chiken from cull chicken meat (Gallus gallus domesticus) - Reyes, Femina Grace Basco
A study on the development of an acceptable canned corned chicken product using cull chicken meat as the primary raw material was undertaken. Phase I dealt with the improvement of the formulation of corned cull chicken. It involves deletion, addition and changes in the amount of some ingredients. Results of the sensory evaluation showed that deleting the beef and adding more cull chicken meat to the formulation resulted to a more uniform color. The use of fresh garlic was replaced by 1.0% garlic powder for convenience and equal distribution to the product. Salt level was lowered down to 1.8% for the fact that the addition of the garlic powder somehow increased the saltiness of the product. Onion powder was added was added as well for flavor. Results of Phase II showed that processing for 60 minutes at 250°F rendered the product commercially sterile, thus, safe for consumption. Furthermore, pre-cooking the product for 10 minutes was also found to give the product the desired firm but tender texture. A bench scale production was conducted in Phase III to test the standard formulation, procedure and thermal process showing the repeatability of the process. Cost analysis showed that the product weighing 240±10 grams can be sold at a price of P38.51. The consumer acceptability test on the product revealed that the consumers found the product to be of very good quality and with an acceptability score which corresponded to like moderately.